Les genres décrits n° 1 - Lucy Michel (Glad!)
The first section of this series concentrates on the ways sex and grammatical gender are described in (French unilingual) reference grammar books, as well as on the ways these descriptions mould discourses and beliefs about masculine and feminine within the French langage. The recurrence of the same « facts » and the same « regularities » contributes to the construction of apparent « truths » about language, that are often seen as basic and unquestionable. The solidity of these constructed truths reinforces, even today, the non acceptance of linguistic change.